Single chamber atrial pacing: an underused and cost-effective pacing modality in sinus node disease. Issue 4 (1st October 1998) - Clarke, K W; Connelly, D T; Charles, R G
Abstract : Objective: To determine the safety and cost effectiveness of single chamber atrial pacing in patients with sinus node disease. Design: Retrospective follow up study. Setting: Tertiary referral centre. Patients: 81 patients with single chamber atrial pacemakers implanted between 1992 and 1996. Main outcome measures: The development of high grade atrioventricular block resulting in a further pacemaker procedure. The cost savings of changing our current pacing practice to conform with British Pacing and Electrophysiology Group guidelines. Results: During the follow up period, four patients (5.8%) required a further procedure to upgrade their atrial pacemaker to a dual chamber system owing to the development of high grade atrioventricular block. In 1995 and 1996, 343 pacemakers were implanted in patients with sinus node disease; 19 (5.5%) received single chamber atrial pacemakers and 271 (79%) dual chamber pacemakers. If the current pacing practice was changed so that all patients received single chamber atrial pacemakers, with revision for symptomatic atrioventricular block, savings in excess of £206 000 would have been made in the two year period. Conclusions: Atrial pacing in patients with sinus node disease is underused. The need for patients to undergo further procedures owing to the development of atrioventricular block is small and significant cost savings could be made by changing pacemaker practice.